Pancasila and Citizenship Education as Non-Military National Defense Development for Generation 5.O - Lailatul Qurrota Ayuni; Dinie Anggraeni Dewi; Muhammad Irfan Adriansyah (Beginner: Journal of Teaching and Education Management, 2024)
This article discusses the importance of Pancasila and citizenship education as part of the development of non-military national defense for generation 5.O, which is the millennial generation that has different characteristics and challenges from previous generations. This study aims to identify the role and contribution of Pancasila and citizenship education in fostering the spirit of national defense in generation 5.O. The research method used is qualitative with a literature study approach. The results of the study show that Pancasila and citizenship education have a very important role in shaping the attitude, values, and awareness of nationality and statehood in generation 5.O. Through this education, generation 5.O is able to understand and implement the values of Pancasila, such as mutual cooperation, democracy, social justice, unity, and solidarity, as well as responsibility to the state. Pancasila and citizenship education also play a role in fostering the spirit of national defense. Generation 5.O needs to be trained to have a love of the homeland, an awareness of the importance of national security and defense, and active participation in national development. In this regard, Pancasila and citizenship education can present self-development programs, such as leadership training, social activities, introduction to local culture, and so on. This article also provides recommendations to strengthen Pancasila and citizenship education as part of the curriculum of secondary and higher education. In addition, there needs to be collaboration between educational institutions, government, and society in implementing education and training programs that support the development of non-military national defense for generation 5.O. Thus, it is expected that generation 5.O will be able to become citizens who have national values, national defense, and contribute positively to national development.